Evaluating the Skeletal Age of Children on the Basis of Bone Size - Florkowski, Andrzej; Kozłowski, Tomasz (Anthropological Review, 1994)
The paper describes a method of identifying the age of children at the moment of death on the basis of measurements of the following bones: clavicle, humerus, ulna, radius, femur, tibia, fibula, scapula, ilium, ischium and pubic bones. The material consists of skeletons of children from an early-mediaeval cemetery in Gruczno. Mean values of measurements and standard deviations of particular classes of age are displayed in tables (Tables 1-13). Non-typical measurements are illustrated in Fig. 1, while growth curves of the analysed bones are presented in Figs 2-14. The presented method allows us to identify the child's age on the basis of a single bone.